Systemic complications associated with bacterial tracheitis. Issue 3 (March 1996) - Britto, J; Habibi, P; Walters, S; Levin, M; Nadel, S
Abstract : The toxic shock syndrome, septic shock, pulmonary oedema, and the acute respiratory distress syndrome (ARDS) were recognised in four children with bacterial tracheitis. ARDS has not previously been reported in association with bacterial tracheitis. Prompt recognition of the severe systemic complications of bacterial tracheitis could lead to a decrease in the morbidity and mortality of this condition.